Appearance and performance factors associated with muscle building supplement use and favourable attitudes towards anabolic steroids in adolescent boys - Piplios, Olivia; Yager, Zali; McLean, Siân A.; Griffiths, Scott; Doley, Jo R. (Frontiers in Psychology, 2023)
The demand for appearance and performance enhancing substances, including muscle building supplements and anabolic androgenic steroids, is increasing in Australia. However, little is known about the associations between appearance and performance-based factors and appearance and performance enhancing substances (APES), particularly among adolescent boys. This study sought to examine a) the prevalence of muscle building supplement use in a sample of adolescent boys and b) how both performance and appearance factors relate to muscle building supplement use and favourable attitudes towards anabolic androgenic steroids in this sample. N=488 adolescent boys aged 13-16 (Mage = 14.59) from nine Australian schools completed measures of supplement use, favourable attitudes towards using steroids, muscle dissatisfaction, body fat dissatisfaction, mesomorphic ideal internalisation, weight training, and sports participation. Hierarchical logistic regressions were used to examine cross-sectional correlates of muscle building supplement use and favourable attitudes towards using anabolic androgenic steroids. In the past three months, 12.7% of the sample had used muscle building supplements. Both appearance and performance-related factors -mesomorphic ideal internalisation and weight training -were related to muscle building supplement use. Only one appearance-related factor -body dissatisfaction -was related to favourable attitudes towards anabolic androgenic steroids. The findings from this study are important as they may help to guide intervention strategies regarding appearance and performance enhancing substance use by Australian adolescent boys, with the ultimate goal of ensuring this population's safety.